PRESENÇA DO VÍRUS SARS-COV-2 EM ÁGUAS SUPERFICIAIS E SUBTERRÂNEAS - CAROLINE BURILLE MORETTI (2023)
The presence of the SARS-CoV-2 virus in sewage samples and both surface and underground water bodies makes the Covid-19 pandemic also an environmental problem. Several authors, in different countries, have documented the presence of the genetic material of the SARS-CoV-2 virus in bodies of water that receive sewage disposal, with or without treatment. In this work, samples of both surface and groundwater were evaluated aiming to characterize their vulnerability to the SARS-CoV-2 virus. The study was carried out in a River Basin placed in an urban context. Water samples were analyzed to identify the presence or absence of the vírus’ genetic material and regarding the water quality. Traces of SARS-CoV-2 RNA were found in all sampled points and cycle threshold (Ct) values ranged from 25.45 to 30.37. The concentration of Escherichia coli and Total Coliforms was above the recommended level at all sampled points, except in the piezometers, which showed a negative result. The detection of SARS-CoV-2 genetic material in the piezometers can serve as an alert to the presence of viruses in groundwater and the necessity to include viruses as one of the parameters of water quality analysis. Key words: vulnerability, coronavirus, water bodies, sewage.